Coconut Shell Activated Carbon with βeta-Silicon Carbide Reinforced Polymer Composites: An Alternative Dielectric Material for Microwave Absorber - Been, Seok Yew; Fwen, Hoon Wee; Saiful Bahri, Mohamed; Martini, Muhamad (2017)
The effect of adding natural based activated carbon, namely coconut shell activated carbon (CSAC) on the structural and dielectric properties of beta-silicon carbide (β-SiC) reinforced polymer composites were investigated. This work aims to assess the potential of using CSAC as conductive filler in the β-SiC based dielectric material used for microwave absorber. Material characterization of the CSAC in term of elemental composition, particle morphology and structural analysis have been performed by using carbon, hydrogen, nitrogen, sulfur (CHNS) elemental analyzer, scanning electron microscope (SEM) and X-ray Diffractometer (XRD). Room temperature open-ended coaxial line method was performed to determine the dielectric properties over broad band frequency of 200 MHz - 20 GHz by using Agilent 85070E Dielectric Probe Kit and Agilent E8362B PNA series network analyzer. The microwave conductivity of the composites was evaluated based on the measured dielectric properties. Experimental result shows that CSAC is highly carbonaceous material with 83.94% of carbon composition and presence of macroporous structure with particle porosity ranging from 446.6nm to 2.5μm was detected. The XRD pattern of coconut shell activated carbon revealed that presence of broad diffraction peaks are detected at 2ϴ= 23.985° and 44.015°, which corresponded to amorphous structure. With the addition of CSAC, it was found that the dielectric properties of the β-SiC composites show improved dielectric properties (ε’ and ε”) starting from 6.18 GHz to 20 GHz. Both real and imaginary parts of permittivity of the composites decrease with increasing frequency, which present the typical dielectric relaxation characteristic. The presence of CSAC increases the composite electrical conductivity at microwave frequency. This indicates that the natural activated carbon, CSAC could thus be used as conductive filler not only for their dielectric losses performance, but also for their cost effective production.